Application of a four-flanged intrascleral fixation technique for toric and multifocal intraocular lenses - Whang, Woong-Joo (Am J Ophthalmol Case Rep, 2020)
PURPOSE: To report clinical outcomes of a four-flanged intrascleral fixation technique using toric and multifocal intraocular lens. OBSERVATIONS: We describe two cases of premium intraocular lens (IOL) implantation after which the patients fully recovered their visual function following a four-point sutureless scleral fixation technique via a 2.8-mm corneal incision. In the first case, a monofocal toric hydrophobic lens consisting of two haptic plates with four holes for suturing was fixated with 5–0 polypropylene monofilament. In the second case, a bifocal hydrophobic lens with the same haptic design was fixated. No conjunctival or scleral sutures, glue, or flap formation was required during the surgery. There were no complications related to the surgical process. CONCLUSIONS AND IMPORTANCE: A four-flanged intrascleral fixation technique may benefit patients with poor zonular support who have high expectations for postoperative visual quality.